2012
DOI: 10.1093/abbs/gms077
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton-dependent pathways for ADMA-induced NF-κB activation and TGF-β high expression in human renal glomerular endothelial cells

Abstract: Asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase inhibitor, is considered to be an independent risk factor in the progression of chronic kidney diseases (CKD). It can induce kidney fibrosis by increasing transforming growth factor (TGF)-β1 expression, but its molecular mechanism is unclear. The aim of the present study was to investigate the role of actin cytoskeleton in ADMA-induced TGF-β1 high expression in human renal glomerular endothelial cells (HRGECs). The structure of stress fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The concentrations of ADMA used in this study were similar to those previously reported [21,29], and were much higher than those in the plasma of patients. For the in vitro experiments, the duration was limited; therefore, a low dose of ADMA (5 mM), similar to that observed in uremia patients, failed to activate the NF-kB (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…The concentrations of ADMA used in this study were similar to those previously reported [21,29], and were much higher than those in the plasma of patients. For the in vitro experiments, the duration was limited; therefore, a low dose of ADMA (5 mM), similar to that observed in uremia patients, failed to activate the NF-kB (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…25,26,75,76,80,81 At the same time, it has been reported that NF-kB activation induces TGF-b production. [82][83][84] Thus, there is a potential positive feedback mechanism between TGF-b production and NF-kB activation that enhances the fibrotic process. (vi) Furthermore, we used RT-qPCR and protein detection by western blot to demonstrate that H 2 O 2 induces the expression and secretion of TGF-b1 and TGF-b2, and it has been clearly demonstrated that TGF-b1 and TGF-b2 induce the conversion of ECs into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that TGF-b is a very important inducer of PRMT1 in inflammation. Although there is no direct evidence to prove the relationship between TGF-b and PRMT1, a study on renal fibrosis was found that ADMA, as an endogenous endothelial NO synthase and inducible NO synthase competitive inhibitor (17,18), can reduce the NO concentration in serum in asthmatic animals (7); furthermore, ADMA is also involved in proline metabolism, which may play an important role in the pulmonary remodeling process through raising collagen synthesis (19). In our study, the supplementation of TGF-b to basic medium increased the expression of PRMT1 in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%